Investigation of Cellular Interactions of Lipid-Structured Nanoparticles With Oral Mucosal Epithelial Cells - Jeitler, R.; Glader, C.; Tetyczka, C.; Zeiringer, S.; Absenger-Novak, M.; Selmani, A.; Fröhlich, E.; Roblegg, E. (Frontiers in Molecular Biosciences, 2022)
Lipid-based nanosystems enable intracellular delivery of drugs in the oral cavity for the treatment of local diseases. To rationally design such systems, suitable matrix compositions and particle properties need to be identified, and manufacturing technologies that allow reproducible production have to be applied. This is a prerequisite for the reliable and predictable performance of in-vitro biological studies. Here, we showed that solid lipid nanoparticles (SLN, palmitic acid) and nanostructured lipid carriers (NLC, palmitic acid and oleic acid in different ratios) with a size of 250 nm, a negative zeta potential, and a polydispersity index (PdI) of less than 0.3 can be reproducibly prepared by high-pressure homogenization using quality by design and a predictive model. SLN and NLC were colloidally stable after contact with physiological fluid and did not form agglomerates. The in-vitro studies clearly showed that besides particle size, surface charge and hydrophobicity, matrix composition had a significant effect. More specifically, the addition of the liquid lipid oleic acid increased the cellular uptake capacity without changing the underlying uptake mechanism. Regardless of the matrix composition, caveolin-mediated endocytosis was the major route of uptake, which was confirmed by particle localization in the endoplasmic reticulum. Thus, this work provides useful insights into the optimal composition of lipid carrier systems to enhance the intracellular uptake capacity of drugs into the oral mucosa.